1989
DOI: 10.1136/bmj.298.6670.372
|View full text |Cite
|
Sign up to set email alerts
|

A mobile surgery for single homeless people in London.

Abstract: Little is known about the social and medical characteristics of people who regularly sleep rough, or whether medical care can be targeted at these people. In 1987 a mobile surgery was used to provide primary health care at two sites in central London where many single homeless people sleep outdoors. One hundred and forty six patients were seen with illnesses ranging from scabies to osteomyelitis and tuberculosis. Sociodemographic data showed the patients to be generally an isolated group with deprived and unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In London, Ramsden (1989) found that only 39% of those interviewed were registered with a GP, and even then, consultations rarely occurred. In Sheffield, however, over two-thirds of those interviewed were registered with a GP.…”
Section: Policy and Politicsmentioning
confidence: 97%
“…In London, Ramsden (1989) found that only 39% of those interviewed were registered with a GP, and even then, consultations rarely occurred. In Sheffield, however, over two-thirds of those interviewed were registered with a GP.…”
Section: Policy and Politicsmentioning
confidence: 97%
“…On one hand, those patients have barriers to access healthcare such as: social isolation, temporary accommodation in a speci c area, suspicion of traditional health services, lack of awareness about how to register with a general practitioner, di culty to cope with waiting rooms and appointment systems. On the other hand, general practitioners may stigmatize marginalized populations 4 . These obstacles may make marginalized unable or unwilling to access public primary care, creating an unful lled gap between patients and healthcare 5 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of National Health Service (NHS) initiatives emerged to supplement mainstream primary care services. Examples included primary health care on the street (Ramsden et al ., 1989) and in hostels (Maclean and Naumann, 1979), and health advocate services for homeless families (Reilly et al ., 2004).…”
Section: Introductionmentioning
confidence: 99%